Competencies of inclusive teachers. Reflections on initial teacher training between expectations and proofs - Fabio Bocci; Ines Guerini; Alessia Travaglini (Firenze University Press, 2021)
The theme of support teachers' competencies continues to be one of the issue still debated when school is intended as a vector for promoting inclusive processes. In line with this debate, the authors of this paper - after a brief reflection on the issue - discuss some data relating to the expectations of a group of trainees attending the 5th cycle of Specialization for support teaching. In particular, trainees were asked which competencies they expect to acquire during the training course in order to increase their professionalism and become inclusive teachers. As indicated in the paper, among these competencies emerge the management ones and those relating to teaching methodologies which, according to trainees, must be flexible and creative. Not surprisingly, their responses highlight that the acquisition of specific skills - which aim at promoting inclusion - is the main motivation that led them to attend the course, despite many of them have already being teachers for some time.    Le competenze dell'insegnante inclusivo. Riflessioni sulla formazione iniziale tra aspettative e conferme Il tema delle competenze dei docenti specializzati per il sostegno continua ad essere uno dei nodi intorno al quale ruota il dibattito sulla scuola come vettore per promuovere processi inclusivi. Nel solco di questo dibattito, gli autori del presente contributo, dopo una breve riflessione sulla questione, presentano alcuni dati relativi alle aspettative che i corsisti del V ciclo di Specializzazione per il sostegno esprimono circa le competenze che si attendono di acquisire durante il percorso formativo al fine di accrescere la propria professionalità e divenire docenti inclusivi. Come indicato nell'articolo, tra queste emergono quelle gestionali e quelle relative alle metodologie didattiche che a loro dire devono essere flessibili e creative. Non a caso, emerge chiaramente dalle loro risposte che l'acquisizione di competenze specifiche mirate a favorire l'inclusione è la motivazione principale che li ha spinti a frequentare il corso, pur essendo molti di loro già insegnanti di scuola da diverso tempo.